The characteristics and formation mechanism of double-band radar echoes formed by a severe rainfall occurred in the Sichuan Basin under the background of two vortices coupling - Dong, YuanChang; Li, GuoPing; Jiang, XingWen; Wang, YuanCheng (Frontiers in Earth Science, 2022)
During 29-30 UTC June 2013, a severe rainfall event with a long and narrow region of strong precipitation occurred in the central of the Sichuan Basin(SCB). Under the combined influence of a Tibet Plateau vortex(TPV) and a southwest vortex(SWV), two banded strong radar echoes existed and developed simultaneously over the SCB. The analysis reveals that the vertical wind shear(VWS) caused by the circulations of the TPV and the SWV was the dominant factor of the formation and development of the radar echoes over the SCB. During coupling period of the two vortices, the SWV provided abundant water vapor at the middle and lower levels over the SCB and the updrafts of the two vortices break through that formed deep convection, which made the precipitation in the SCB reached the maximum intensity. The enhancement of horizontal vorticity caused by the baroclinicity and the secondary circulation related to the two vortices created conditions for the formation of the double-band radar echoes. The matching degree of water vapor and heating conditions accompanying the circulation of the two vortices could affect the developments of convective storms and precipitation.